Estudo e desenvolvimento de sensores a fibra óptica para a análise e controle de vibrações em máquinas elétricas e estruturas - Linessio, Rafael Pomorski (2020)
Vibration analysis is one of the main techniques used to identify the behavior of structures and electrical machines. In both areas, there is a need to monitor and identify the components in frequency. In structure monitoring, the alteration of frequencies can be related to the stiffness variation and, consequently, the defect identification. In electrical machines, based on the vibration spectrum, it is possible to identify failures in the rotor, stator, and bearings. The influence of the electromagnetic field in electrical machines, long distances, and atmospheric discharges when analyzing large buildings suggests developing new sensors, providing a promising area for applying optical sensors. Thus, in this work, a biaxial optical accelerometer is developed using fiber Bragg gratings (FBGs) with a high numerical aperture (UHNA). The steps development of the accelerometer is defined as project, characterization, calibration, and testing. The resonance frequency and sensitivity of the transducer is 1250.00 Hz and 100 pm.g−1, respectively. The tests are carried out with and without the load on the analyzed motor axis. This allows for validation of the biaxial optical accelerometer response for monitoring the frequencies of vibrations in electrical machines. In addition, the vibration control technique is proposed in this work, based on the neutralizers, coupled with optical sensing. For the analysis of vibration neutralizers, a passive spring-mass (MK), spring-mass-damping (MKC), the semi-active and hybrid pendulum-type model is implemented to control vibration in a building in scale. The MK neutralizer is tuned to the building’s first natural frequency. For the MKC neutralizer, the viscoelastic material C-1002 is used, which sets a control in the range of 1.45 Hz to 1.71 Hz. The semi-active neutralizer is implemented based on the feedback topology, having the FBG as sensor. For validation of this sensor in vibration control analysis, the response is compared with the piezoelectric sensor. The control range of this system is limited between 1.10 Hz and 1.55 Hz, and the attenuation obtained from the excitation near the natural frequency of the building is 14 dB. The hybrid pendular neutralizer combines the passive and semi-active element’s characteristics, allowing the actuation broadband between 1.10 Hz and 1.65 Hz. Thus, the optical accelerometer development based on UHNA fiber optics and the vibration neutralizers allowed validating these projects and implementing future vibration analysis and control applications.